ANALYSIS OF TARGET COSTING IMPLEMENTATION IN IMPROVING SINGLEFACE PRODUCTION COST EFFICIENCY IN PT. HILAL GEMILANG KHAIR - Ayu, Dian Setyaning; Suhendro, Suhendro; Wijayanti, Anita (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2021)
Competition in the manufacturing world makes companies have to have an accurate strategy in getting the right price in the market. Taking into account the costs incurred during production using the right method in the company can compete with fierce competition. The purpose of this research is to apply the target costing method in order to be able to streamline singleface production costs at PT. Hilal Gemilang Khair. The type of research used is qualitative research. Methods of data analysis using qualitative methods with case study design or case studies. Sources of data used are primary data and secondary data. Collecting data by conducting interviews, observation and documentation. The results showed that before using the target costing method, the costs incurred were Rp. 6,506,55/kg and after applying the target costing method, the cost obtained is Rp. 6,289.52/kg. From the results of the application of the target costing method, the company can make a cost efficiency of Rp. 217.04/kg with a percentage of 3.45%. From the results of the study it can be concluded that PT Hilal Gemilang Khair can apply the target costing method used as a single face production cost control.